Electrically Conductive MoS2 Reinforced Polyacrylonitrile Nanofibers for Biomedical Applications. Issue 4 (23rd December 2021) - Balasubramaniam, Bhuvaneshwari; Arun Kumar, Shreedevi; Singh, Kanwar Abhay; Bhunia, Sukanya; Verma, Kartikey; Tian, Limei; Gupta, Raju Kumar; Gaharwar, Akhilesh K.
Abstract : Molybdenum disulfide (MoS2 ) nanostructures are layered 2D transition metal dichalcogenide with unique physical, chemical, and biological properties. These properties can further be optimized during the synthesis process by introducing atomic defects within the layered nanostructure of MoS2 . Herein, MoS2 nanostructure with varying defect density is synthesized and highly hydrophilic MoS2 nanostructure is shown to be obtained by increasing the atomic defects. This hydrophilic MoS2 nanostructure is further incorporated within electrospun polyacrylonitrile (PAN) nanofibers to improve the physical and chemical properties. Uniform distribution of MoS2 nanoassemblies is observed within the PAN nanofibers. Significant increase in electrical conductivity, thermal stability, and mechanical strength of PAN nanofibers are obtained due to MoS2 addition. Interestingly, the addition of MoS2 nanostructure resulted in enhanced protein adsorption as well as cytocompatibility of these hybrid PAN‐MoS2 nanofibers due to hydrophilic characteristics of MoS2 nanoassemblies. It is expected that these hybrid PAN‐MoS2 nanofibers can potentially be used for a variety of biomedical applications including drug delivery, tissue engineering, and biosensing. Abstract : Polyacrylonitrile (PAN) electrospun nanofibers are reinforced with defect‐rich molybdenum disulfide (MoS2 ) nanostructure to enhance the mechanical, electrical, and biological characteristics. These hybrid PAN‐MoS2 nanofibers can potentially be used for a variety of biomedical applications including drug delivery, tissue engineering, and biosensing.